Comparative efficacy of acupuncture and acupoint catgut embedding in diminished ovarian reserve: A prospective randomized controlled trial: A Prospective Randomized Controlled Trial (Indian Journal of Traditional Knowledge (IJTK), 2025)
Diminished ovarian reserve (DOR) is a significant health issue affecting women, leading to hormonal imbalances and infertility. Traditional Chinese Medicine (TCM) therapy plays a vital role in its treatment. This study aimed to compare the efficacy of traditional acupuncture and acupoint catgut embedding in improving ovarian function in women diagnosed with DOR. A single center randomized controlled trial was conducted with 61 participants aged 18-40 years diagnosed with DOR. Participants were randomly assigned to receive either acupuncture or acupoint catgut embedding. Primary outcomes included changes in follicle-stimulating hormone (FSH), estradiol (E2), anti-Müllerian hormone (AMH), antral follicle count (AFC), and menstrual cycle regularity. Quality of life was assessed using Kupperman scores and SF-36. Intra-group analyses showed significant improvements in FSH (p